Crisis Leadership: A Case Study of New York's 2020 COVID-19 Nursing Home Executive Policy Action. (30th November 2022) - King, Stephen M.
Abstract: Successful crisis leadership hinges upon the expression of moral values and demonstration of leadership competencies. This case study explores New York Governor Andrew Cuomo's COVID-19 nursing home executive policy. Three key leaders' roles are discussed and assessed in the context of the crisis event: Governor Cuomo, Commissioner of Health Howard Zucker, and Stephanie Gilmore, a nursing home care manager. This case study provides a discussion of the New York nursing home executive policy action, focusing largely on the roles and behavior of Cuomo, Zucker, and Gilmore. A brief literature review discusses the meaning and importance of crisis management, moral leadership, and leadership competencies, especially as they apply to this case study. Results demonstrate that effective crisis leadership has components of both moral leadership and various leadership competencies and skills. This case study concludes with limitations and strengths of this case study.